Analisis Tingkat Kerentanan Sosial dan Ekonomi pada Potensi Bencana Tsunami di Desa Ringinrejo Kecamatan Wates Kabupaten Blitar - Effantra Effendi; Yohana Noradika Maharani; Arif Rianto Budi Nugroho; Johan Danu Prasetya; Purbudi Wahyuni; Ficky Adi Kurniawan (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Blitar Regency, which directly borders the Indian Ocean on the south side, has the potential for a tsunami disaster. Ringinrejo Village, Wates District, which is potentially affected by the tsunami disaster, is on the coast of Jolosutro Beach with a population of 334 people. The large population in coastal areas makes social and economic vulnerability an important factor in disaster management. This research aims to analyze social and economic vulnerability per inhabited building block using the SoVI method, analyzing the distribution of social and economic vulnerability using the GIS method, and the dominant factors influencing social and economic vulnerability using the stepwise regression method. The research results show that: (1) the level of social and economic vulnerability is 36.63% at a medium level of vulnerability with 37 households, 28.71% at a low level of vulnerability or 29 households, 26.73% at a high level of vulnerability with 27 houses households, 3.96% at very low and very high levels of vulnerability with 4 households each. The need for involvement of all parties to reduce the potential for a tsunami disaster in Ringinrejo Village, Wates District, Blitar Regency.